Wastewater reuse for livestock feed irrigation as a sustainable practice: A socio-environmental-economic review - Fatima-Zahra Lahlou (16931766) (2021)
Rapid population growth will engender an intensification in agricultural activities which currently utilise most of global freshwater withdrawals, stressing not only the water sector, but also the energy sector due to the increase in demand for energy intensive commercial fertilisers. The global production of fertilisers, in addition to declining worldwide phosphorus reserves may find it difficult to sustain this rising demand at current capacities. As part of sustainable development, farmers will have to adopt alternative resources that balance the environment, economy and society. Wastewater reuse represents an opportunity for this challenge as it can alleviate the stress on scarce water resources and contribute to circular economies. In addition, it contains relatively high amounts of nutrients that can substitute for part of the fertilisation requirements. In the literature, reusing wastewater for agricultural purposes obtained relatively high acceptance rates amongst populations, especially for growing forage crops. This review gathers all the studies that have investigated the reuse of wastewater in growing animal feed. It details the findings based on the social, environmental, and eonomic dimensions of sustainability. This review provides a basis for future fertigation systems as it gathers all the tools required to make a comprehensive assessment of the practice. Interesting research directions include the need to investigate farmers’ concern about consumers’ attitude, which apparently obstructs them from adopting new technologies despite their improved harvests. In addition, it is worth investigating the overall environmental benefits associated with wastewater fertigation on the water-soil and on the water-energy nexus, in terms of global warming potential as reported carbon footprint savings in the literature are undervalued. Finally, there is a strong economic potential associated with the practice in terms of industrial symbiosis that requires further exploration. Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclepro.2021.126331